Criminal Liability against Children as Perpetrators of Theft - Iswantoro Iswantoro; Maryanto Maryanto (Law Development Journal, 2020)
The objectives of this study are: 1. To analyze criminal responsibility towards children as perpetrators of criminal acts of theft in the jurisdiction of the Pati District Court. 2. To analyze constraints in the implementation of criminal responsibility against children as perpetrators of criminal acts of theft in the jurisdiction of the Pati District Court and their solutions. The research method used is juridical empirical. Research results and discussion The background of the crime of theft committed by children is various factors, including; lack of parental attention and supervision. The occurrence of the criminal act of theft, not only raises legal problems but also creates economic problems and social problems in the community, because it is an act that is detrimental to the state and to this act the state reacts with punishment as the last resort (Ultimum Remedium)Accountability for the verdict of case Number: 5 / Pid.Sus-Anak / 2017 / PN Pati, with the defendant WES Known as Wn Bin S having been legally and convincingly proven guilty of committing the crime of "Theft in Aggravating Circumstances"; as regulated and punishable under Article 363 paragraph (1) 4 of the Criminal Code as in the single indictment, imposes a crime against the child of WES Known as W Bin S, in the form of imprisonment for 7 (seven) months at the LPKA (Special Development Institution for Children), arrest and detention that has been served by the child is fully deducted from the sentence imposed, so that the child remains detained, by charging the child a case fee of IDR 2,500 (two thousand and five hundred rupiah).